Trends and differences in alcohol-related mortality rates by gender and by prefectures in Japan between 1995 and 2016. (1st April 2021) - Kinjo, Aya; Purevdorj, Bolormaa; Okada, Tomomi; Kuwabara, Yuki; Fujii, Maya; Higuchi, Susumu; Osaki, Yoneatsu
Abstract: Background: This study aimed to identify increases in 100 % alcohol-related death (ARD) and any differences among prefectures between 1995–2016. Methods: Data from the national death registry on 100 % ARDs between 1995–2016 were extracted. Age-standardized mortality rate (ASMR) of 100 % ARD by year, gender, and gender ratio were calculated. After dividing the period into 1995−2005 and 2006−2016, the ASMRs of 100 % ARDs were calculated by prefecture. Additionally, based on geographical area, municipality size, or annual alcohol sales per adult in each prefecture, prefectures were divided into groups and analysed. Results: In total, 95, 455 deaths were caused by 100 % ARD from 1995–2016. Men's ASMRs of 100 % ARD markedly increased from 4.0 per 100, 000 in 1995 to 5.2 between 2010 and 2013, and gradually declined to 5.0 in 2016. Women's ASMRs increased steadily from 0.3 in 1995 to 0.8 in 2016. The gender ratio of ASMRs decreased from 13.3 in 1995 to 6.3 in 2016. The ASMR of one prefecture, which had reduced alcohol tax rates, was higher for both genders. Both men's and women's ASMRs were higher in the prefectures that had higher alcohol sales (6.3 [5.0–7.7] and 0.8 [0.6–1.1], respectively) compared to the prefectures that had lower alcohol sales (4.3 [4.0–4.7] p < 0.001 and 0.6 [0.5−0.6] p = 0.045, respectively). Conclusions: The ASMR of 100 % ARD remained high for men and increased for women, and prefecture-level higher alcohol sales and lower tax rates correlated with the higher mortality rate. Increasing prices and taxes and reducing alcohol sales may contribute to a decrease in alcohol-related mortality.